Massachusetts Institute of Technology (MIT)-Lemelson Awards Ceremony - The Lemelson Foundation; Massachusetts Institute of Technology (1998)
The MIT-Lemelson Awards are presented to American inventors and innovators by the program of the same name, a partnership between the Massachusetts Institute of Technology and the Lemelson Foundation. The 1998 awards include the Lifetime Achievement award, presented to inventor Jacob Rabinow, and the MIT-Lemelson award presented to biotechnician Robert S. Langer. This was the first year the awards were presented following the death of foundation co-founder Jerome Lemelson, and so the program includes a biographical video tribute and remarks from his wife, Dorothy Lemelson, the foundation's co-founder, and his sons, Eric and Robert.
Keywords: Awards; Massachusetts Institute of Technology; Vest, Charles M.; Lemelson-MIT Awards Program; Lemelson Center; Thurow, Lester C.; Rabinow, Jacob; Lemelson, Jerome, 1923-; Langer, Robert S.; Inventions--Awards